PANDANGAN NAHDLATUL ULAMA TENTANG STATUS KEWARGANEGARAAN NON-MUSLIM DI INDONESIA - Salam, Nursalam; Sabri Samin; Usman Jafar; Nursalam Rahmatullah (ISTIQRA: Jurnal Hasil Penelitian, 2024)
This study aims to enrich and develop understanding of the status of non-Muslim citizenship in Indonesia from the perspective of Nahdlatul Ulama (NU) as the largest community organization in Indonesia. The type of research used is library research, with a theological-normative, sharia and historical approach. This study uses data collection methods in the form of quoting, filtering and analyzing using content analysis of representative literature that is relevant to the problem discussed, then reviewing and concluding it. The results of this study are an analysis of the status of non-Muslim citizenship in Indonesia according to Nahdlatul Ulama categorized as non-Muslim citizens. In fiqh that limits the rights of non-Muslims does not apply in the concept of a nation state implemented in Indonesia. Therefore, this study recommends that political and religious categorization not be monopolized by one particular entity or group. In addition, this study also suggests that the government, the Indonesian Ulema Council (MUI), as well as community organizations such as Nahdlatul Ulama or Muhammadiyah need to re-knit the threads that have become tangled due to identity politics, and reconstruct the understanding of classical fiqh teachings and doctrines into a contemporary perspective that is more in line with the concept of an inclusive nation state, as implemented in Indonesia.